A Survey on Various Techniques to Minimize Routing Overhead in MANET - Tamilselvi, P; Ravi, T.N (International Journal of Computer Sciences and Engineering, 2025)
Wireless ad-hoc network (or) Mobile Ad Hoc Network is a set of mobile nodes in the combination of some computing contrivances which could be placed randomly everywhere in the network to do a specific task inclusive of dispensing and transferring of messages for sundry applications. The nodes can broadcast information in meticulous range and the host is capable of changing their position very repeatedly. If the information is not transferred within a scrupulous moment, retransmission of data packets is done by the protocols, which enhance the communication overhead in MANET. Broadcasting is playing a vital role for path discovery. Most probably, four types of broadcasting methods are used. They are simple flooding, location-predicated methods, probability predicated strategies and Neighbour cognizance predicated. This article exposes a widespread learning and investigation of various routing overhead reducing techniques proposed by many researchers. This paper additionally reveals the routing overhead percentage achieved using the prominent techniques proposed by contemporary researchers